2021
DOI: 10.20546/ijcrbp.2021.801.002
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on the role of herbal medicine for Alzheimer's disease (Dementia)

Abstract: This review paper highlights the use of medicinal plants in the management of Alzheimer's disease and memory deficit. Alzheimer’s disease is the most common form of dementia, a serious brain disorder that impacts daily living through memory loss and cognitive changes. Alzheimer's disease is also age-related neurodegenerative disorders caused by progressive loss of structure or function of neurons, resulting in neuronal cell death. Alzheimer's patients have an acetylcholine deficiency. Stressful conditions, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(144 citation statements)
references
References 134 publications
(706 reference statements)
0
11
0
Order By: Relevance
“…Medicines made from plants have been crucial in the treatment of kidney stone disease (Nagpal and Sharma, 2020;Gauri and Sanjay, 2020;Akram and Idrees, 2019;Amarasiri et al, 2020;Sundaram et al, 2019;Shirani et al, 2020;Khan et al, 2019). Many of these natural products have pharmacological or biological properties that can be used to discover and create new pharmaceutical drugs (Malabadi et al, 2021;Malabadi and Chalannavar, 2020). Patients with kidney stones have the option of utilising herbal treatment as well (Nagpal and Sharma, 2020;Gauri and Sanjay, 2020;Akram and Idrees, 2019).…”
Section: Plant Based Medicine and Treatment For Kidney Stone Diseasementioning
confidence: 99%
“…Medicines made from plants have been crucial in the treatment of kidney stone disease (Nagpal and Sharma, 2020;Gauri and Sanjay, 2020;Akram and Idrees, 2019;Amarasiri et al, 2020;Sundaram et al, 2019;Shirani et al, 2020;Khan et al, 2019). Many of these natural products have pharmacological or biological properties that can be used to discover and create new pharmaceutical drugs (Malabadi et al, 2021;Malabadi and Chalannavar, 2020). Patients with kidney stones have the option of utilising herbal treatment as well (Nagpal and Sharma, 2020;Gauri and Sanjay, 2020;Akram and Idrees, 2019).…”
Section: Plant Based Medicine and Treatment For Kidney Stone Diseasementioning
confidence: 99%
“…are native to the Indian sub-continent and required warm temperatures and high light intensity to achieve good yields . Humans have a long history with Cannabis sativa, with evidence of cultivation dating back as far as 10,000 years (12,82). The World Health Organization (WHO) reported that Cannabis is the most widely cultivated, trafficked and abused illicit drug, and it constitutes over half of worldwide drug seizures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis sativa and Cannabis indica were native of Indian origin found as wild noxious weed in the Indian Himalayan Region and other parts of India (3)(4)(5)(6)(7)(8)(9). Since then, hemp consumption has been spurred on by its wide range of properties and uses from Indian Himalayan civilization to another civilization through consecutive millennia (3)(4)(5)(6)(7)(8)(9)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93). Cannabis research work remains years behind than other crops because of the long legacy of prohibition and stigmatization (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations